# How do you solve #−4(x + 1) − 3 = −3(x − 4) #?

Expand all of the terms, then move all of the factors to one side of the equation, setting it equal to zero.

-4x - 4 - 3 = -3x +12

-x - 19 = 0

-x = 19 x = -19

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation −4(x + 1) − 3 = −3(x − 4), you first distribute the terms inside the parentheses:

-4x - 4 - 3 = -3x + 12

Next, combine like terms:

-4x - 7 = -3x + 12

Now, isolate the variable terms by adding 4x to both sides:

-7 = x + 12

Subtract 12 from both sides:

-19 = x

So, the solution to the equation is x = -19.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you solve #x/4 -3=2#?
- How do you find the simple interest paid after 5 months on a loan of $7,000 borrowed at an annual interest rate of 5%?
- An electric bill in May was $112.00. In June, the bill was $163.00. What is the percent of increase, rounded to the nearest tenth?
- How do you solve and check your solution given #y+7.2=21.9#?
- How do you solve #y/-2+ 5 = -4#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7